2023
DOI: 10.1007/s00520-023-07738-y
|View full text |Cite
|
Sign up to set email alerts
|

“If only I had”, patients’ experiences during early oncology trials

Abstract: Purpose Until today, it is not clear why patients decide to continue with early clinical trial (ECT) participation. Therefore, the aim of this study is to explore to which extent the self-determination theory of Ryan and Deci, according to the ECT enrollment phase, corresponds to the motivations of participants during ECT’s. Methods This study has a qualitative design. Data were collected using semistructured interviews and were deductively analyz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In fact, multiple surveys point to the fact that almost every clinician and patient volunteered for a phase 1 trial with the objective of a clinical response, 1,2 in addition to altruistic motive. 3 A review of published phase 1 trials reported ORRs ranging from 4% to 12.2%, [4][5][6][7][8][9][10][11] and CBRs ranging from 24% to 53%. [6][7][8][9][10][11] The selection of patients for phase 1 trials remains challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, multiple surveys point to the fact that almost every clinician and patient volunteered for a phase 1 trial with the objective of a clinical response, 1,2 in addition to altruistic motive. 3 A review of published phase 1 trials reported ORRs ranging from 4% to 12.2%, [4][5][6][7][8][9][10][11] and CBRs ranging from 24% to 53%. [6][7][8][9][10][11] The selection of patients for phase 1 trials remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…However, secondary objectives, such as overall response rate (ORR; calculated as partial response [PR] plus complete response [CR]) and clinical benefit rate (CBR; calculated as stable disease plus ORR), are equally important end points. In fact, multiple surveys point to the fact that almost every clinician and patient volunteered for a phase 1 trial with the objective of a clinical response, in addition to altruistic motive . A review of published phase 1 trials reported ORRs ranging from 4% to 12.2%, and CBRs ranging from 24% to 53% …”
Section: Introductionmentioning
confidence: 99%